HUBUNGAN FUNGSI PERENCANAAN KEPALA RUANGAN DENGAN KINERJA PERAWAT DI RSU MAYJEN H.A THALIB KOTA SUNGAI PENUH - Eliza, Eliza; Pelani, Helman; Sartika, Sri (Ensiklopedia of Journal, 2024)
Nursing services have great leverage to achieve development goals in the health sector. Nursing as a professional staff is responsible for providing nursing services according to the competence and authority possessed independently or in collaboration with members of the health team. The aim of the research was to identify the relationship between the planning function of the head of the room and the performance of the executive nurse at RSU Mayjen H. AThalib, Sungai Full City in 2023. This research used a cross sectional approach, with a sample size of 65 people. Variables were analyzed univariately and bivariately with SPSS. The research results showed that the largest age group was 20 – 29 years (49.2%), gender was mostly female (80%), educational level was mostly DIII Nursing (69.2%), working period 1 – 5 years (53.8% ). Civil servant employment status (50.8%) THL (49.2%). More than half (56.9%) stated that the planning function of the head of the room was good. The performance of 41 nurses (63.1%) was good. The results of the Fisher Exact Test statistic were p = 0.000 (p<0.05), (OR) 3.919 times greater for carrying out the planning function compared to respondents with good performance. Conclusion: There is a relationship the planning function of the head of the room with the performance of the implementing nurse at the Mayjen H.A Talib Regional Hospital, Sungai Banyak City. Nursing staff are expected to improve their performance in providing nursing care services so that the quality of hospital services increases in accordance with community expectations and hospital service management.Keywords: Management, Planning, Nursing, Performance